Reshaping museum space : architecture, design, exhibitions - Macleod, Suzanne (Museum meanings., 2005)
"Reshaping Museum Space pulls together the views of an international group of museum professionals, architects, designers and academics, highlighting the complexity, significance and malleability of museum space, and provides reflections upon recent developments in museum architecture and exhibition design. The problems of navigating the often contradictory agendas and aspirations of the broad range of professionals and stakeholders involved in any new project are discussed in various chapters that concentrate on the process of architectural and spatial reshaping. Contributors review recent new build, expansion and exhibition projects, questioning the types of museum space required at the beginning of the twenty-first century and highlighting a range of possibilities for creative museum design."--Jacket